Glycemic and insulinemic responses to six cereal products in healthy adults - Ciok, J; Dzieniszewski, J; Lang, V (Central European Journal of Public Health, 2004)
Glycemic index (GI) and insulin index (II) scores of six cereal-based foods (biscuits and shortbreads) were determined and the relationship between the glycemic and insulin responses of the foods was examined. The study was conducted using recommended by FAO/WHO methodology using glucose as a standard food. We obtained a range of GI scores from 49 to 68% and II scores from 51 to 75%. The test foods’ blood insulin responses were in parallel to their glycemic responses although in every case the level of II was higher than the level of GI. The foods’ II scores were closely related to their GI scores (r=0.80).
Keywords: dospělí; Female; Edible Grain; jedlá semena; Adult; ženské pohlaví; Food Analysis; nutriční hodnota; lidé; Blood Glucose; postprandiální období; Nutritive Value; Insulin; analýza potravin; Male; Postprandial Period; mužské pohlaví; inzulin; krevní glukóza; Humans